Estudo meta-analítico do desempenho de bovinos de corte em pastagens tropicais - Tambara, Antônio Augusto Cortiana (2011)
Animal performance was evaluated in bovine cattle livestock systems using tropical pasture based diets through a meta-analysis process, which included a database of scientific articles, dissertations and theses. Data was tabulated and categorized identifying the scientific work, the experiment, animals, animal performance, pasture, supplements and grazing. The conversion efficiency of supplement use was evaluated in the studies containing control (no supplementation), and calculated as the change in average daily gain of individual weight (CoEfADGan) or area (ha, CoEfADGha) per kg of supplement offered. Data distribution from a general database was assessed. To analyze the factors affecting animal performance variables the general database was sub-divided into two sub-bases, rainy and dry season. To evaluate the factors affecting animal performance variables data was weighted by n treatments and analysis of variance and covariance was used. The average daily gain of body weight per animal (ADGan, 0.870 vs. 0.611 kg / animal / day) and per hectare (ADGha vs. 5.76. 4.59 kg / ha / day), as well as daily animal load per hectare (DALha, 1483 vs. 1211 kg / ha / day) were higher (P <0.05) during the rainy season than during the dry season. During the rainy season, ADGan was lower in the genus Brachiaria and superior in the Panicum (P <0.05), but the DALha and ADGha were higher (P <0.05) in Cynodon. In dry season, ADGan was lower (P <0.05) in the Brachiaria than in Cynodon and Panicum, and ADGha was higher (P <0.05) in Panicum. In both dry and rainy seasons, ADGan, ADGha and DALha increased linearly (P <0.01) with increasing levels of supplementation, which ranged from zero to 1.6% of live weight (LW). The ADGan increased linearly (P <0.05) and DALha decreased linearly (P <0.05), while ADGha was quadratically (P <0.05) related to the increased availability of herbage. Animal performance was linear and positively correlated with leaf: stem proportion from pastures (P <0.05), both in the rainy and dry seasons. During the rainy season the best responses in ADGan and ADGha were obtained from the use of protein supplement compared with supplemental energy or proteinated salt (P <0.05), while the use of energy supplement enabled a higher DALha (P <0,05). During the dry season, ADGha was not affected by supplement type, but the best responses were obtained for ADGan with energy supplement (P <0.05) while protein supplementation, either through proteinated salt or protein supplement, was associated with a higher DALha (P <0.05). During the rainy season animal performance was quadratically (P <0.05) related to live weight (LW) of animals, and ADGan maximized in animals weighing about 380 kg and ADGha maximized in animals weighting about 400 kg. In the dry season, ADGan and ADGha were linearly and positively related animal LW (P <0.05). Pasture neutral detergent fiber (NDF) content ranged from 46 to 82% in dry matter (DM) and was quadratically related to ADGan (P <0.05) being that maximum gain was obtained with NDF content around 66%. Crude protein (CP) of pasture ranged from 1.9 to 21.6% in DM and was linear and positively correlated with ADGan (P <0.05). The ADGan was linear and negatively associated with the value obtained by the ratio between the content (% DM) of total digestible nutrients (TDN) and CP of pasture (P <0.05). Nitrogen fertilizer was linearly (P <0.05) associated with increased DALha, both in the rainy and dry seasons. The CoEfADGan and the CoEfADGha decreased lineally (P <0.05) with increasing animal LW during the rainy season, becoming negative from around 360 kg. In the rainy season as well as in the dry season, both efficiencies were also negatively (P <0.05) related to the CP content of pasture, being also negative from 10% CP, and positive and quadratically (P <0.05) related to the leaf: stem ratio of the pastures. Highest efficiencies were observed with leaf: stem ratio 3.7:1. During the dry season EfCoGMD and EfCoGAD decreased (P < 0.05) with the increasing the value obtained by the TDN: CP supplement ratio, becoming negative from 4,3:1. In conclusion, the meta-analysis enabled the identification of beef cattle performance in tropical pastures showing that it is influenced in an integrated manner by factors associated with several features such as climate, pasture, animal, handling and supplementation. However, the degree to which each factor influences animal performance could be more accuratelly assessed if publications were standardized and contained essential information regarding more detailed methodological descriptions and basic statistical information.